Serum protein-hyaluronic acid complex nanocarriers: Structural characterisation and encapsulation possibilities. (1st January 2021) - Kovács, Alexandra N.; Varga, Norbert; Juhász, Ádám; Csapó, Edit
Graphical abstract: Highlights: Quantitative characterisation of hyaluronic acid - bovine serum protein interaction. Design of new serum protein/hyaluronic acid drug carriers with core-shell structure. Mass ratios of macromolecules and the pH have dominant effect on carrier formation. Abstract: A protein-polysaccharide-based potential nanocarrier system have been developed via a simple, one-step preparation protocol without the use of long-term heating and the utilization of hardly removable crosslinking agents, surfactants, and toxic organic solvents. To the best of our knowledge, this article is the first which summarizes in detail the pH-dependent quantitative relationship between the bovine serum albumin (BSA) and hyaluronic acid (HyA) confirmed by several physico-chemical techniques. The formation of colloidal complex nanoconjugates with average diameter of ca . 210–240 nm is strongly depend on the pH and the applied BSA:HyA mass ratio. Particle charge titrations studies strongly support the core-shell type structure, where the BSA core is covered by a thick HyA shell. Besides the optimization of these conditions, the drug encapsulation capacity and the dissolution profiles have been also studied for ibuprofen (IBU) and 2-picolinic acid (2-PA) as model drugs.